2018
DOI: 10.1111/dom.13296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exenatide once weekly plus dapagliflozin, exenatide once weekly alone, or dapagliflozin alone added to metformin monotherapy in subgroups of patients with type 2 diabetes in the DURATION‐8 randomized controlled trial

Abstract: This analysis assessed whether responses with exenatide once weekly plus dapagliflozin (n = 231), exenatide once weekly alone (n = 230), or dapagliflozin alone (n = 233) differed in key patient subpopulations of the DURATION‐8 trial. Potential treatment‐by‐subgroup interactions for changes in glycated haemoglobin (HbA1c) and body weight after 28 weeks were evaluated among subgroups determined by baseline HbA1c, age, sex, body mass index, type 2 diabetes duration, race, ethnicity and estimated glomerular filtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Furthermore, a converse relationship between weight loss and baseline HbA 1c levels was observed, whereby increasing baseline HbA 1c was associated with greater reductions in HbA 1c but a decreasing magnitude of weight loss. A similar pattern has been observed with liraglutide as an add-on to insulin treatment, 41 with exenatide alone 42 and with dulaglutide. 31 32 These findings have relevance for clinical practice, indicating that there may be an effect with GLP-1RAs (and potentially other antihyperglycaemic therapies) in predicting treatment responses based on HbA 1c levels.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, a converse relationship between weight loss and baseline HbA 1c levels was observed, whereby increasing baseline HbA 1c was associated with greater reductions in HbA 1c but a decreasing magnitude of weight loss. A similar pattern has been observed with liraglutide as an add-on to insulin treatment, 41 with exenatide alone 42 and with dulaglutide. 31 32 These findings have relevance for clinical practice, indicating that there may be an effect with GLP-1RAs (and potentially other antihyperglycaemic therapies) in predicting treatment responses based on HbA 1c levels.…”
Section: Discussionsupporting
confidence: 73%
“…Seven RCTs with 1913 patients were included in the systematic review and meta-analysis ( Figure 1). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Of these, two studies were retrieved as conference abstracts and one study was identified in ClinicalTrials.gov (NCT02964247). 25,28 Of note, for one of these conference abstracts and for the trial from ClinicalTrials.gov, we utilized post hoc data from their respective journal articles, which were published shortly after our search date.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…A head-tohead comparative randomized controlled trial (RCT) showed superiority of exenatide once weekly (EOW) vs dapagliflozin when added to metformin monotherapy, 9 especially in patients with CKD. 10 However, a network meta-analysis comparing GLM, added after dualtherapy failure, suggested no significant difference in the glycaemic effects of GLP-1RAs and SGLT2is. 11 In addition to lowering HbA1c, both GLP-1RAs and SGLT2is significantly improve body weight (BW) and blood pressure (SBP).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, GLP‐1RAs are supposed to be more effective in lowering glucose than are SGLT2is. A head‐to‐head comparative randomized controlled trial (RCT) showed superiority of exenatide once weekly (EOW) vs dapagliflozin when added to metformin monotherapy, especially in patients with CKD . However, a network meta‐analysis comparing GLM, added after dual‐therapy failure, suggested no significant difference in the glycaemic effects of GLP‐1RAs and SGLT2is .…”
Section: Introductionmentioning
confidence: 99%